Prediction of airflow rate passing through compressible wet fiber web in vacuum dewatering for energy conversion improvement. Issue 3 (13th February 2023) - Ren, Peng; Han, Ying; Fang, Xiangjun; Jiao, Zeyu
Abstract: Vacuum dewatering is a highly energy-intensive process that is widely adopted in industrial production such as papermaking and chemical manufacture. A significant portion of the energy consumed by vacuum system is converted into energy that drives airflow passing through the wet fiber web. During the energy conversion process, a part of the energy is wasted due to the redundant capacity of the vacuum pump, which is caused by the deviation of the airflow rate estimation during the design of the vacuum system. To improve the energy conversion rate, a variable porosity model (VPM) is proposed in this study to better simulate the process of airflow passing through a porous medium–wet fiber web. Compared with the existing constant porosity model (CPM), the VPM model takes the effect of wet fiber web compressibility into account to improve the accuracy of airflow rate calculation. Different sets of experimental data demonstrate that the accuracy of airflow calculation of the VPM is about 22 times that of the CPM. In addition, the characteristic parameterization of different fiber structures in this study expands the applicability of the model and can be widely adopted in multitudinous industrial fields, which is of great significance for improving the energy conversion rate of vacuum dewatering process and saving energy.